CLONING AND EXPRESSION OF FUSION PROTEIN GLUTATHION S TRANSFERASE-STREPTAVIDIN ON Bacillus subtilis SPORES AND EVALUATION OF ITS SPECIFIC BINDING WITH BIOTINYLATED ANTIBODY CETUXIMAB - Thu Thuỷ, Bùi; Trang, Phan Huong; Hieu, Nguyen Trang; My, Tran Thi; Nghia, Phan Tuan; Van Anh, Nguyen Thi (Vietnam Journal of Science and Technology, 2015)
We cloned fusion gene (cotB-gst-streptavidin), coding three sequential proteins including membrane spore coat protein CotB, Glutathion S Transferase (GST), and streptavidin, into the chromosome of Bacillus subtilis PY79 to create recombinant strain named SA2. Expression of streptavidin on the outer coat of SA2 spores were confirmed by immunofluoresence using specific anti-streptavidin rabbit IgG and anti-rabbit IgG labeled Alexa546. The specific bindings of biotinylated cetuximab on spores of Bacillus subtilis SA1 (expressing CotB-streptavidin) and on Bacillus subtilis SA2 were detected by Western Immunoblotting. The data indicates that binding of biotinylated cetuximab on SA2 spores was slightly 1.4 fold higher than that on SA1 spores, suggesting limited role of GST in enhancing the exposure of streptavidin for interaction with biotinylated cetuximab.   Keywords: Bacillus subtilis spore; Glutathion S Transferase (GST), streptavidin, biotinylated